Transcriptome Analysis of Peripheral Blood Mononuclear Cells in Pulmonary Sarcoidosis - Yoshioka, Keiichiro; Sato, Hironori; Kawasaki, Takeshi; Ishii, Daisuke; Imamoto, Takuro; Abe, Mitsuhiro; Hasegawa, Yoshinori; Ohara, Osamu; Tatsumi, Koichiro; Suzuki, Takuji (Frontiers in Medicine, 2022)
Background: Sarcoidosis is a granulomatous systemic disease of unknown etiology. Mononuclear cells such as macrophages or lymphocytes in lung tissue and hilar or mediastinal lymph nodes have been recognized to play an essential role in granuloma formation in pulmonary sarcoidosis. Peripheral blood mononuclear cells (PBMCs) consist of several immunocompetent cells and have been shown to play a mechanistic role in the pathogenesis of sarcoidosis. However, the genetic modifications that occur in bulk PBMCs of sarcoidosis remain to be elucidated. Purpose: This study aimed to explore the pathobiological markers of sarcoidosis in PBMCs by comparing the transcriptional signature of PBMCs from patients with pulmonary sarcoidosis with those of healthy controls by RNA sequencing. Methods: PBMC samples were collected from subjects with pulmonary sarcoidosis with no steroid/immunosuppressant drugs (n = 8) and healthy controls (n = 11) from August 2020 to April 2021, and RNA sequencing was performed with the PBMC samples. Results: Principal component analysis using RNA sequencing datasets comparing pulmonary sarcoidosis with healthy controls revealed that the two groups appeared to be differentiated, in which 270 differentially expressed genes were found in PBMCs between sarcoidosis and healthy controls. Enrichment analysis for gene ontology suggested that some biological processes related to the pathobiology of sarcoidosis, such as cellular response to interleukin (IL)-1 and IFN-γ, regulation of IL-6 production, IL-8 secretion, regulation of mononuclear cell migration, and response to lipopolysaccharide, were involved. Enrichment analysis of the KEGG pathway indicated the involvement of tumor necrosis factor (TNF), toll-like receptor signaling, IL-17 signaling pathways, phagosomes, and ribosomes. Most of the genes involved in TNF and IL-17 signaling pathways and phagosomes were upregulated, while most of the ribosome-related genes were downregulated. Conclusion: The present study demonstrated that bulk gene expression patterns in PBMCs were different between patients with pulmonary sarcoidosis and healthy controls. The changes in the gene expression pattern of PBMCs could reflect the existence of sarcoidosis lesions and influence granuloma formation in sarcoidosis. These new findings are important to strengthen our understanding of the etiology and pathobiology of sarcoidosis and indicate a potential therapeutic target for sarcoidosis.